2015
DOI: 10.1111/cen3.12269
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and their potential roles in diseases of the nervous system

Abstract: Autoantibodies are found in many disorders of the nervous system, including diseases affecting the peripheral nervous system (e.g. Guillain-Barr e syndrome and other peripheral neuropathies), the central nervous system (e.g. neuromyelitis optica, multiple sclerosis and limbic encephalitis) and the neuromuscular junction (e.g. myasthenia gravis), as well as in neuropsychiatric disorders and in paraneoplastic syndromes. Some of these antibodies are likely to play an important pathogenic role in disease developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 157 publications
(291 reference statements)
0
9
0
Order By: Relevance
“…There are many ways in which anti-PLP antibodies, particularly those targeting epitopes on the extracellular surfaces of oligodendrocytes or myelin, could potentially have an impact in MS, including mechanisms such as complement-mediated lysis, antibody mediated cell cytotoxicity, modulation of cell architecture, opsonization of myelin or myelin debris leading to increased activation of phagocytic cells ( 19 ). In a C3H/HeJ mouse model in which demyelinating disease can be induced by immunization with PLP 190−209 , we have previously reported that mice that can make a T cell response, but not an antibody response, develop lesions in the brainstem, but not in the cerebellum, whereas in the presence of both T cells and antibodies specific for PLP 190−209 there is development of lesions in both the brainstem and the cerebellum ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways in which anti-PLP antibodies, particularly those targeting epitopes on the extracellular surfaces of oligodendrocytes or myelin, could potentially have an impact in MS, including mechanisms such as complement-mediated lysis, antibody mediated cell cytotoxicity, modulation of cell architecture, opsonization of myelin or myelin debris leading to increased activation of phagocytic cells ( 19 ). In a C3H/HeJ mouse model in which demyelinating disease can be induced by immunization with PLP 190−209 , we have previously reported that mice that can make a T cell response, but not an antibody response, develop lesions in the brainstem, but not in the cerebellum, whereas in the presence of both T cells and antibodies specific for PLP 190−209 there is development of lesions in both the brainstem and the cerebellum ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous published studies have reported antibodies directed against myelin proteins (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) or other CNS antigens (13)(14)(15)(16)(17)(18) in CSF or serum of MS patients, but only a small number of these studies have attempted to determine whether these antibodies are potentially pathogenic (3,7,15,18). In some cases, antibodies in MS patients may be merely an epiphenomenon; however, there are multiple examples in the non-MS literature of how antibodies targeting CNS tissues can be directly pathogenic (reviewed in (19)), and the chance that antibodies present in at least some patients with MS are pathogenic is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…In disorders affecting the nervous system, autoantibodies can exert pathogenic effects via a wide range of mechanisms, including antibody-mediated cell lysis, opsonisation of target proteins for attack by macrophages, crosslinking of Fc receptors, blocking or removing receptors involved in neurotransmission or cellular homeostasis or blocking of repair mechanisms (Beasley and Greer, 2015). It is possible for more than one of these mechanisms to be active in the same disease.…”
Section: Potential Functional (Pathogenic) Effects Of Antibodies Targmentioning
confidence: 99%
“…Given the findings in the current chapter, another potential future direction would be to transfect cells with the glutamate transporter molecules against which some patient sera appear to show strong antibody reactivity, and screen much larger panels of sera. Finally, it has to be remembered that the potential functional roles of autoantibodies in MS and other autoimmune demyelinating diseases don't necessarily stop at complement-mediated ADCC or opsonization: there are many other ways in which antibodies could act (recently reviewed in Beasley and Greer, 2015), and it may be necessary to investigate those before we gain a full understanding of the role of autoantibodies in diseases such as MS.…”
Section: 4mentioning
confidence: 99%
“…Therefore, even though an antibody might be directed against an epitope that has the correct specificity, it will not be able to induce complement-mediated lysis if it is not of an isotype that can bind complement. However, such antibodies might be able to act in other ways, for example by opsonization of target proteins for attack by macrophages, crosslinking of Fc receptors, blocking or destroying receptors involved in cellular homeostasis, and blocking of repair mechanisms such as remyelination (recently reviewed in Beasley and Greer, 2015).…”
Section: Principal Findings Of the Thesismentioning
confidence: 99%